Fatty acids as biofuel precursors accumulation : an investigation by metabolic engineering approach - Chen, Liwei (2015)
Production of biofuels derived from microbial fatty acids has attracted great attention in recent years owing to their potential to replace petroleum-derived fuels. To be cost competitive with current petroleum fuel, production of the direct precursor fatty acids need to be enhanced to approach high yields.